Comparison and suitability of SRTM and ASTER digital elevation data for terrain analysis and goemorphometric parameters: Case study of Sungai Patah subwatershed (Baram River, Sarawak, Malaysia) - Dodge-Wan, Dominique; Vijith, H. (2015)
Determination of suitability of satellite-derived elevation data sets in terrain characterisation in a tropical region was carried out on the Sungai Patah subwatershed in the interior of Sarawak, East Malaysia. The goal was to facilitate rapid assessment of topographic variables and spatial parameters related to the morphometric aspects of the region. The freely available SRTM (90 m) and ASTER (30 m) elevation data sets were compared and used to generate spatial and aspatial parameters. The cross-validation of SRTM and ASTER elevation surfaces with toposheet-derived elevation for 200 random points shows root mean squared errors (RMSE) of ± 35.08 m and ± 44 m, respectively. The spatial and aspatial parameters derived show certain major and minor variations in the outputs, which can be attributed to the differences in spatial and spectral resolutions of the data acquisition systems. The results and the findings of the present study suggest that both SRTM and ASTER elevation data sets can be used for terrain characterisation in regions similar to the study area, by replacing the traditional toposheet-derived elevation surfaces. However, minor errors are present when either set is used independently. This can be avoided by the concurrent use of SRTM and ASTER elevation data sets, which will reduce data errors and artefacts in both data sets and improve the accuracy of terrain variables and watershed parameters derived from them.